2020
DOI: 10.3389/fpls.2020.01098
|View full text |Cite
|
Sign up to set email alerts
|

Genome Editing of eIF4E1 in Tomato Confers Resistance to Pepper Mottle Virus

Abstract: Many of the recessive virus-resistance genes in plants encode eukaryotic translation initiation factors (eIFs), including eIF4E, eIF4G, and related proteins. Notably, eIF4E and its isoform eIF(iso)4E are pivotal for viral infection and act as recessive resistance genes against various potyviruses in a wide range of plants. In this study, we used Clustered Regularly Interspaced Palindromic Repeats/CRISPR-associated protein 9 (CRISPR/ Cas9)-mediated targeted mutagenesis to test whether novel sequence-specific mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 63 publications
(88 reference statements)
1
32
0
1
Order By: Relevance
“…Furthermore, basic information about factors required for viral infection identified in heterologous hosts has been used to engineer resistance in crops. Based on the observation that eukaryote translation initiation factors are susceptibility genes to potyviruses [ 5 ], through interaction with potyviral VPg [ 28 ], CRISPR-Cas9 was used in tomato to engineer resistance to pepper mottle virus by editing eIF4E1 [ 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, basic information about factors required for viral infection identified in heterologous hosts has been used to engineer resistance in crops. Based on the observation that eukaryote translation initiation factors are susceptibility genes to potyviruses [ 5 ], through interaction with potyviral VPg [ 28 ], CRISPR-Cas9 was used in tomato to engineer resistance to pepper mottle virus by editing eIF4E1 [ 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CRISPR/Cas9-mediated mutation of SlJAZ2 , the closest tomato ortholog of Arabidopsis JAZ (JASMONATE ZIM DOMAIN) repressor AtJAZ2 , also significantly increased tomato resistance to Pto DC3000, the causal agent of tomato bacterial speck disease (Ortigosa et al 2019 ). Pepper mottle virus (PepMoV) is a potyvirus that can infect tomato plants (Melzer et al 2012 ), and the CRISPR/Cas9-mediated mutation of tomato eIF4E1 , which encodes a eukaryotic translation initiation factor and is a recessive resistance gene against potyviruses (Wang 2015 ), conferred tomato resistance to PepMoV (Yoon et al 2020 ). Interestingly, a stably engineered CRISPR/Cas9 system by targeting virus genes encoding coat protein (CP) or replicase (Rep) has been generated in tomato, and these tomato transgenic plants also showed significantly increased resistance to the infection of tomato yellow leaf curl virus (TYLCV) (Tashkandi et al 2018 ).…”
Section: Applications Of Genome Editing In Tomato Improvementmentioning
confidence: 99%
“…In Capsicum spp., pvr1 and pvr3 have been characterized as two unlinked recessive loci that confer distinct kinds of resistance to PepMoV [104]. The pvr1 gene, which was identified in C. chinense PI159236 and PI152225, confers relatively broad resistance to Pep-MoV, TEV, and PVY [22,81]. In contrast, the pvr3 gene, which was identified in C. annuum 'Avelar', confers a different type of resistance to PepMoV than to TEV and PVY [104].…”
Section: Recessive Resistance Genesmentioning
confidence: 99%
“…Variation in symptoms, pathogenicity, and molecular properties among PepMoV isolates in Korea suggested that certain virus-encoded proteins determine host specificity or pathogenicity [4,19]. Recent studies of compatible/incompatible responses between PepMoV and host plants revealed dynamic interactions between PepMoV-encoded viral proteins and host proteins [20][21][22]. The development of full-length infectious clones of PepMoV has enabled researchers to investigate the interaction between PepMoV and hosts as well as to explore the feasibility of using PepMoV as a viral vector for the stable expression of heterologous genes in plants [23,24].…”
Section: Introductionmentioning
confidence: 99%